Efficiency of complex medical and psychological aid system for women with neurotic anxiety and depressive disorders of different psycho-genesis - Spylovyj, Ya. V. (Journal of Education, Health and Sport, 2017)
Objective: to substantiate approaches and develop principles of integrated medical and psychological aid to the women with neurotic anxiety and depressive disorders, caused by modern psycho-traumatic factors, taking into account the peculiarities of their clinical manifestations and mechanisms of formation. Contingent and methods. 200 women have been examined: 150 persons had agitation and depressive disorders of the neurotic register (78 of them were internally displaced persons (IDP) and 72 were spouses of military men of the ATO-troops), 25 persons had endogenous depression and 25 were mentally health women. Clinical, psychopathological and psychodiagnostic methods were used. The research was carried out on the basis of the Lviv Regional Clinical Psychiatric Hospital. Results. The study presented resulted in updating of clinical picture and mechanisms of neurotic agitation formation, depression disorders in the women under study. Neurotic disorders had their own specificity which depends on psychological injury factor. In general, IDP - women took in the worse sense the traumatic circumstances than the spouses of the military men participating in the military operations. The basic principles of providing comprehensive medical and psychological assistance to the contingent under study have been identified. On the basis of the generalization of the data obtained, the principles and the structure of the medical and psychological components of the complex care were differentiated depending on the severity of the anxiety and depressive manifestations and difficulties of functioning. The system developed is effective in the aspects of reducing psychopathological symptoms and improving the quality of the patients’ life.